EVALUASI IMPLEMENTASI PRINSIP EKOWISATA BERBASIS MASYARAKAT DALAM PENGELOLAAN CLUNGUP MANGROVE CONSERVATION SUMBERMANJING WETAN, MALANG - Husamah Husamah; Atok Miftachul Hudha (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Clungup Mangrove Conservation (CMC) is a new ecotourism destination managed by a community group called 'Bhakti Alam Sendang Biru'. This study aimed to analyze the implementation of the 5 principles of Community-based Ecotourism in the management of CMC, namely: (1) Conservation principle (Nature conservation principle, 6 criterias and culture conservation, 4 criterias), (2) Community participation principle (7 criterias), (3) Economic principle (5 criterias), (4) Education principle (5 criterias), and (5) Tourism principle (6 criterias). This research method is descriptive qualitative. Source of the data obtained are primary data obtained through observation to the site to conduct an interview to the informants and secondary data obtained through the study of literature and documents. The data obtained were processed with descriptive techniques. The results showed that in general the 5 principles of community-based ecotourism have been implemented in the management of CMC although some criteria for each principle there is not yet implemented, is being planned, pursued, and optimized.